Morphology of the female Myrmecolacidae (Strepsiptera) including the apron, and an associated structure analogous to the peritrophic matrix - Kathirithamby, J (Oxford University Press, 2000)
Development in the totally endoparasitic female Strepsiptera has been clarified by light and electron microscopy. At the end of the 4th instar the cuticle sclerotizes anteriorly to form the cephalothorax and collar, the former of which is later extruded through the host cuticle. Posteriorly, the cuticle remains unsclerotized, and this region is within the host. The moult to the neotenic adult takes place within the 4th instar cuticle, and the epicuticles of the previous instars are retained as persistent sheaths. The gut, which is present in the earlier endoparasitic stages, is lost after extrusion of the cephalothorax, and a novel structure develops on the ventral surface of the neotenic female. Due to the position of this novel structure in the neotenic female, this area is called an apron. The detailed structure of the membranes in the apron in Stichotrema dallatorreanum Hofeneder from Oro Province, and of another female myrmecolacid (which has a different host) from West New Britain in Papua New Guinea, is described. A dual function for the apron is proposed.